Ruthenium-based composite catalyst for catalyzing oxidation of hydrogen chloride to prepare chlorine and application of ruthenium-based composite catalyst
By supporting ruthenium on alumina, titanium oxide and silicon oxide composite support, and using colloid milling and graphene oxide dispersion technology, an efficient ruthenium-based composite catalyst is formed, which solves the catalytic activity and stability of catalytic hydrogen chloride preparation of chlorine gas by catalytic hydrogen chloride oxidation. The problem of insufficient results has achieved efficient hydrogen chloride conversion and chlorine selectivity.
Patent Information
- Application Number
- CN202411401680.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-09
- Publication Date
- 2025-01-10
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of catalytic oxidation, and in particular relates to a ruthenium-based composite catalyst for catalyzing the oxidation of hydrogen chloride to produce chlorine. Background Art
[0002] Chlorine is an important yellow-green basic chemical raw material, which is widely used in medicine, pesticides, electronics and industry. Chlorine is an important raw material for the production of inorganic chemical products such as sodium hypochlorite, aluminum chloride, ferric chloride, bleaching powder, bromine, phosphorus trichloride, etc. It is also used to produce organic chlorides such as chloroacetic acid, epichlorohydrin, monochlorobenzene, etc. In addition, chlorine is also a raw material for the production of chloroprene rubber, plastics and plasticizers. In the daily chemical industry, it is mainly used to produce synthetic sodium alkyl sulfonate and sodium alkylbenzene sulfonate. In most chlorine application fields, the utilization rate of chlorine is only half, and only one chlorine element in the chlorine molecule is used, and the other chlorine element forms hydrogen chloride. The added value of hydrogen chloride is low, and the application of by-product hydrogen chloride has become a problem for many chlorine-related industries.
[0003] The catalytic oxidation of hydrogen chloride to produce chlorine is an important means to achieve efficient utilization of hydrogen chloride and chlorine circulation. Therefore, the research and development of catalysts for hydrogen chloride oxidation is of great significance.
[0004] In recent years, many research institutions have conducted extensive research on catalysts for hydrogen chloride oxidation. Chinese Patent 202210943074.3 discloses the application of a copper-lanthanum alloy catalyst in the preparation of chlorine by hydrogen chloride oxidation. The catalyst is based on copper and doped with lanthanum active components. It shows good catalytic activity in the hydrogen chloride oxidation reaction mixed with organic impurities. Under the reaction conditions, the conversion rate of hydrogen chloride is 55-88%. Due to the presence of organic matter in the system, the catalyst will produce carbon deposits after running for a period of time, which may affect the activity of the catalyst. The conversion rate of hydrogen chloride on the catalyst still needs to be further improved. Chinese Patent 201910195575.6 discloses a method for preparing a highly active hydrogen chloride oxidation catalyst. The catalyst uses molecular sieves and titanium oxide composites as carriers, ruthenium as an active component, and a large amount of organic compounds (templates, sulfur-containing compounds) are added to the catalyst during preparation. A certain amount of waste gas and pollution will be generated during subsequent roasting. Although the activity of the catalyst is relatively high, the stability still needs to be further investigated. Chinese patent 201711220899.8 discloses a method for preparing a hydrogen chloride oxidation catalyst, which directly adds a powder carrier to an aqueous solution of a ruthenium precursor, stirs it thoroughly, and then oxidizes it with hydrogen peroxide, and obtains a catalyst after solid-liquid separation, drying and calcination. Although the method is simple and efficient in preparing the catalyst, the activity of the catalyst is low and the conversion rate of hydrogen chloride is low (less than 35.9%). The reason may be that the dispersion effect of ruthenium on the composite carrier is not good and the utilization rate of ruthenium is low. Summary of the invention
[0005] In view of the defects of the prior art, the present invention provides a ruthenium-based composite catalyst for catalyzing the oxidation of hydrogen chloride to produce chlorine, which has the characteristics of high ruthenium utilization rate and good catalyst activity and stability.
[0006] The ruthenium-based composite catalyst for catalyzing the oxidation of hydrogen chloride to produce chlorine provided by the present invention is a composite carrier of aluminum oxide, titanium oxide and silicon oxide on which ruthenium is supported. The mass content of Ru in the catalyst is 1% to 1.9%, and the mass ratio of titanium oxide, aluminum oxide and silicon oxide in the composite carrier is 1:0.8-1.5:0.2-0.3.
[0007] The preparation method of the ruthenium-based composite catalyst of the present invention comprises the following steps:
[0008] Step 1: Add aluminum sol with a mass concentration of 20% to a colloid mill for grinding, then add titanium oxide and silicon oxide powder, continue grinding for 30 to 60 minutes, then add pseudo-boehmite and silica sol and continue grinding for 30 to 60 minutes to obtain a slurry; apply the slurry on a ceramic plate, place it in a drying and roasting integrated furnace for heat treatment, the heat treatment is first low-temperature treatment and then high-temperature treatment, the low-temperature treatment temperature is 200 to 400°C, the time is 2 to 4 hours, and the high-temperature treatment temperature is 600 to 800°C, and the time is 2 to 4 hours; after the heat treatment, scrape off the titanium aluminum silicon oxide on the ceramic plate and seal it for storage.
[0009] Step 2: Add the graphene oxide aqueous solution to a colloid mill for grinding, then add Tianqing powder or starch, continue grinding for 30 to 60 minutes, then add hydrated ruthenium trichloride, and continue grinding for 30 to 60 minutes; then add the titanium aluminum silicon oxide in step 1 to the colloid mill and continue grinding for 30 to 60 minutes, the grinding temperature is controlled at 4 to 10°C, and then the grinding temperature is increased to 94 to 98°C, the solution is concentrated, and as the water evaporates, the solution gradually becomes viscous and finally forms a slurry.
[0010] Step 3: Coat the slurry obtained in step 2 on a ceramic plate, and treat it in a drying and roasting integrated furnace under nitrogen protection at 260-320°C for 1-3 hours, then introduce hydrogen so that the hydrogen accounts for 5%-20% of the total volume of nitrogen and hydrogen, maintain the constant temperature for 4-8 hours, then turn off the hydrogen, continue to introduce nitrogen for 6-10 hours, then introduce air into the nitrogen, keep the temperature unchanged for oxidation, and obtain an unformed catalyst.
[0011] Step 4: Scrape the unformed catalyst obtained in step 3 off the ceramic plate, add forming liquid, and press into tablets or extrude into strips. After forming, place it in a drying and calcining integrated furnace for calcination at a temperature of 260 to 320°C, maintain for 4 to 10 hours, and cool to room temperature to obtain a formed ruthenium-based composite catalyst.
[0012] In the above step 1, the grinding temperature is preferably 4-10°C.
[0013] In the above step 1, the mass ratio of the aluminum sol, titanium oxide, silicon oxide, pseudo-boehmite and silica sol is preferably 1.0-2.5:1:0.15-0.25:0.7-1.5:0.08-0.3.
[0014] In the above step 2, the mass concentration of the graphene oxide aqueous solution is preferably 2% to 4%, and when concentrated, the volume of the slurry is 20% to 30% of the volume of the initial solution.
[0015] In the above step 2, preferably, the amount of the sesbania powder or starch added is 0.2% to 0.6% of the mass of titanium aluminum silicon oxide, and the amount of the graphene oxide aqueous solution added is 9 to 11 times the mass of titanium aluminum silicon oxide.
[0016] In the above step 3, the initial concentration of the air introduced is preferably 10% of the total volume of air and nitrogen, and the air is increased by 10% every 1 hour until pure air is introduced, keeping the temperature unchanged, and the pure air is maintained for 12 to 24 hours before cooling to room temperature to complete the oxidation.
[0017] In the above step 4, the mass percentage composition of the molding liquid is preferably: 0.5% Tianqing powder or starch, 2% to 3% aluminum sol, 1% to 3% silica sol, 3% to 5% hydrochloric acid and the remainder water; the amount of molding liquid added is 5% to 34% of the mass of the unmolded catalyst.
[0018] The present invention also provides an application of the above-mentioned ruthenium-based composite catalyst to catalyze the oxidation of hydrogen chloride to prepare chlorine. The specific method is: the ruthenium-based composite catalyst is loaded into a fixed bed reactor, air is introduced, and the reaction temperature is raised to 310-350°C at the same time, the reaction pressure is controlled from normal pressure to 0.1MPa, the air is replaced by oxygen (with a purity greater than 99%), and after the temperature and pressure are stabilized, hydrogen chloride gas is introduced, the volume ratio of oxygen to hydrogen chloride gas is maintained at 1.5-3:1, and the mass space velocity of hydrogen chloride gas (relative to the catalyst) is 0.6-0.8h / min. -1 Oxygen and hydrogen chloride gas undergo oxidation reaction on the catalyst to generate chlorine. The preferred heating rate is 1 to 3°C / min.
[0019] The beneficial effects of the present invention are as follows:
[0020] 1. The present invention adopts a colloid mill for grinding and mixing in the catalyst preparation, which can control the size of solid particles in the liquid phase to below 1 μm, thereby achieving full mixing of the components.
[0021] 2. The present invention ingeniously utilizes the dispersing, supporting and spacing effects of graphene oxide to fully disperse ruthenium. The dispersion degree of Ru on the catalyst is more than 38%, the utilization rate of Ru is higher, and the catalyst cost can be effectively reduced.
[0022] 3. The catalyst of the present invention undergoes three stages of low-temperature pyrolysis, hydrogen reduction and air oxidation during preparation, thereby achieving the immobilization of Ru on the catalyst, avoiding aggregation and sintering in subsequent reactions, and improving the stability of the catalyst.
[0023] 4. The catalyst of the present invention is used for catalyzing the oxidation of hydrogen chloride to produce chlorine, the conversion rate of hydrogen chloride can reach up to about 95%, and the selectivity of chlorine is 100%. DETAILED DESCRIPTION
[0024] The present invention is further described in detail below in conjunction with embodiments, but the protection scope of the present invention is not limited to these embodiments.
[0025] Implementation 1
[0026] The mass content of Ru in the ruthenium-based composite catalyst of this embodiment is 1.2%, the mass ratio of titanium oxide, aluminum oxide and silicon oxide in the composite carrier is 1:0.9:0.2, and the preparation method of the catalyst is as follows:
[0027] Step 1: Add 600g of aluminum sol with a mass concentration of 20% into a colloid mill for grinding at a grinding temperature of 4°C, then add 470g of titanium oxide and 80g of silicon oxide powder, continue grinding for 40 minutes, then add 405g of pseudo-boehmite (aluminum oxide content is 75%) and 70g of silica sol with a mass concentration of 20% and continue grinding for 40 minutes to obtain a slurry; apply the slurry on a ceramic plate, place it in a drying and roasting integrated furnace for heat treatment, that is, first keep it at 300°C for 3h, and then keep it at 600°C for 3h; after heat treatment, scrape off the titanium aluminum silicon oxide on the ceramic plate and seal it for storage.
[0028] Step 2: Add 9000g of a 3% graphene oxide aqueous solution to a colloid mill for grinding, then add 5g of starch, continue grinding for 40min, then add 32.4g of hydrated ruthenium trichloride (ruthenium content is 37%), and continue grinding for 40min; then add 988g of titanium aluminum silicon oxide obtained in step 1 to the colloid mill and continue grinding for 40min, the grinding temperature is 4°C; then increase the grinding temperature to 95°C, concentrate the solution, and as the water evaporates, the solution gradually becomes viscous, and the volume of the final slurry is 20% to 30% of the initial solution volume.
[0029] Step 3: Coat the slurry obtained in step 2 on a ceramic plate, and in a drying and calcining integrated furnace under nitrogen protection, introduce hydrogen after treating at 300°C for 2 hours, so that hydrogen accounts for 10% of the total volume of nitrogen and hydrogen, and keep the constant temperature for 5 hours, then turn off the hydrogen, keep the constant temperature and nitrogen introduction, add air to the nitrogen after 6 hours, and keep the temperature unchanged for oxidation. The initial concentration of the introduced air is 10% of the total volume of air and nitrogen, and the air is increased by 10% every 1 hour until pure air is introduced, and the temperature is kept unchanged. After the pure air is maintained for 12 hours, it is cooled to room temperature to complete the oxidation and obtain an unformed catalyst.
[0030] Step 4: Scrape the unformed catalyst obtained in step 3 off the ceramic plate, add 6% of the mass of the unformed catalyst into a forming liquid, press the tablets, and place them in a drying and calcining integrated furnace for calcining at a temperature of 300°C for 6 hours, and then cool to room temperature to obtain a formed catalyst. The mass percentage of the forming liquid is: 0.5% starch, 2% aluminum sol, 2% silica sol, 3% hydrochloric acid and 92.5% water.
[0031] Evaluation of the catalytic performance of the ruthenium-based composite catalyst in this example: The ruthenium-based composite catalyst was crushed and sieved, and particles between 10 and 20 meshes were loaded into a fixed bed reactor, and air was introduced. At the same time, the reaction temperature was increased to 310°C, and the reaction pressure was controlled to be 0.01 MPa. The air was replaced with oxygen. After the temperature and pressure were stabilized, hydrogen chloride gas was introduced, and the volume ratio of oxygen to hydrogen chloride gas was maintained at 1.6:1. The mass space velocity of hydrogen chloride gas was 0.7 h / min. -1 , oxygen and hydrogen chloride gas undergo oxidation reaction on the catalyst to generate chlorine. The results show that the conversion rate of hydrogen chloride is 93.2% and the selectivity of chlorine is 100%.
[0032] Example 2
[0033] The mass content of Ru in the ruthenium-based composite catalyst of this embodiment is 1.7%, the mass ratio of titanium oxide, aluminum oxide and silicon oxide in the composite carrier is 1:0.8:0.2, and the preparation method of the catalyst is as follows:
[0034] Step 1: Add 550g of aluminum sol with a mass concentration of 20% into a colloid mill for grinding at a grinding temperature of 5°C, then add 491.5g of titanium oxide and 80g of silicon oxide powder, continue grinding for 30 minutes, then add 377g of pseudo-boehmite (aluminum oxide content is 75%) and 91.5g of silica sol with a mass concentration of 20% and continue grinding for 30 minutes to obtain a slurry; apply the slurry on a ceramic plate, place it in a drying and roasting integrated furnace for heat treatment, that is, first keep it at 400°C for 3h, and then keep it at 700°C for 3h; after heat treatment, scrape off the titanium aluminum silicon oxide on the ceramic plate and seal it for storage.
[0035] Step 2: Add 10000g of 2% graphene oxide aqueous solution to a colloid mill for grinding, then add 2g of sesbania powder, continue grinding for 30min, then add 45.9g of hydrated ruthenium trichloride (ruthenium content is 37%), and continue grinding for 30min; then add 983g of titanium aluminum silicon oxide obtained in step 1 to the colloid mill and continue grinding for 30min, the grinding temperature is 5°C; then increase the grinding temperature to 95°C, concentrate the solution, as the water evaporates, the solution gradually becomes viscous, and the volume of the final slurry is 20% to 30% of the initial solution volume.
[0036] Step 3: Coat the slurry obtained in step 2 on a ceramic plate, and in a drying and calcining integrated furnace under nitrogen protection, introduce hydrogen after treating at 260°C for 2 hours, so that hydrogen accounts for 8% of the total volume of nitrogen and hydrogen, and keep the constant temperature for 4 hours, then turn off the hydrogen, keep the constant temperature and nitrogen introduction, add air to the nitrogen after 6 hours, and keep the temperature unchanged for oxidation. The initial concentration of the air introduced is 10% of the total volume of air and nitrogen, and the air is increased by 10% every 1 hour until pure air is introduced, and the temperature is kept unchanged. After the pure air is maintained for 12 hours, it is cooled to room temperature to complete the oxidation and obtain an unformed catalyst.
[0037] Step 4: scrape the unformed catalyst obtained in step 3 off the ceramic plate, add 30% of the mass of the unformed catalyst into a forming liquid, perform extrusion molding, and place it in a drying and roasting integrated furnace for roasting after molding. The roasting temperature is 320°C, maintained for 4 hours, and then cooled to room temperature to obtain a formed catalyst. The mass percentage composition of the molding liquid is: 0.5% sesbania powder, 3% aluminum sol, 1% silica sol, 4% hydrochloric acid and 91.5% water.
[0038] Evaluation of the catalytic performance of the ruthenium-based composite catalyst in this example: The ruthenium-based composite catalyst was crushed and sieved, and particles between 10 and 20 meshes were loaded into a fixed bed reactor, and air was introduced. At the same time, the reaction temperature was increased to 330°C, and the reaction pressure was controlled to be 0.02 MPa. The air was replaced with oxygen. After the temperature and pressure were stabilized, hydrogen chloride gas was introduced, and the volume ratio of oxygen to hydrogen chloride gas was maintained at 1.7:1. The mass space velocity of hydrogen chloride gas was 0.6 h -1 , oxygen and hydrogen chloride gas undergo oxidation reaction on the catalyst to generate chlorine. The results show that the conversion rate of hydrogen chloride is 95.5% and the selectivity of chlorine is 100%.
[0039] Example 3
[0040] The mass content of Ru in the ruthenium-based composite catalyst of this embodiment is 1.0%, the mass ratio of titanium oxide, aluminum oxide and silicon oxide in the composite carrier is 1:1.4:0.3, and the preparation method of the catalyst is as follows:
[0041] Step 1: Add 750g of aluminum sol with a mass concentration of 20% into a colloid mill for grinding at a grinding temperature of 8°C, then add 366.7g of titanium oxide and 90g of silicon oxide powder, continue grinding for 30 minutes, then add 484g of pseudo-boehmite (aluminum oxide content of 75%) and 100g of silica sol with a mass concentration of 20% and continue grinding for 30 minutes to obtain a slurry; apply the slurry on a ceramic plate, place it in a drying and roasting integrated furnace for heat treatment, that is, first keep it at 200°C for 3h, and then keep it at 600°C for 3h; after heat treatment, scrape off the titanium aluminum silicon oxide on the ceramic plate and seal it for storage.
[0042] Step 2: Add 10000g of a 4% graphene oxide aqueous solution into a colloid mill for grinding, then add 4g of sesbania powder, continue grinding for 30min, then add 27g of hydrated ruthenium trichloride (ruthenium content is 37%), and continue grinding for 30min; then add 990g of titanium aluminum silicon oxide obtained in step 1 into the colloid mill and continue grinding for 30min, the grinding temperature is 8°C; then increase the grinding temperature to 95°C, concentrate the solution, and as the water evaporates, the solution gradually becomes viscous, and the volume of the final slurry is 20% to 30% of the initial solution volume.
[0043] Step 3: Coat the slurry obtained in step 2 on a ceramic plate, and in a drying and calcining integrated furnace under nitrogen protection, introduce hydrogen after treating at 280°C for 1 hour, so that hydrogen accounts for 5% of the total volume of nitrogen and hydrogen, and keep the constant temperature for 6 hours, then turn off the hydrogen, keep the constant temperature and nitrogen introduction, add air to the nitrogen after 6 hours, and keep the temperature unchanged for oxidation. The initial concentration of the air introduced is 10% of the total volume of air and nitrogen, and the air is increased by 10% every 1 hour until pure air is introduced, and the temperature is kept unchanged. After the pure air is maintained for 12 hours, it is cooled to room temperature to complete the oxidation and obtain an unformed catalyst.
[0044] Step 4: Scrape the unformed catalyst obtained in step 3 off the ceramic plate, add 5% of the mass of the unformed catalyst into a forming liquid, press the tablets, and place them in a drying and calcining integrated furnace for calcination after forming. The calcination temperature is 260°C, maintained for 6 hours, and then cooled to room temperature to obtain the formed catalyst. The mass percentage composition of the forming liquid is: 0.5% starch, 2% aluminum sol, 1% silica sol, 3% hydrochloric acid and 93.5% water.
[0045] Evaluation of the catalytic performance of the ruthenium-based composite catalyst in this example: The ruthenium-based composite catalyst was crushed and sieved, and particles between 10 and 20 meshes were loaded into a fixed bed reactor, and air was introduced. At the same time, the reaction temperature was increased to 320°C, and the reaction pressure was controlled to be 0.01 MPa. The air was replaced with oxygen. After the temperature and pressure were stable, hydrogen chloride gas was introduced, and the volume ratio of oxygen to hydrogen chloride gas was maintained at 1.5:1. The mass space velocity of hydrogen chloride gas was 0.7 h / min. -1 , oxygen and hydrogen chloride gas undergo oxidation reaction on the catalyst to generate chlorine. The results show that the conversion rate of hydrogen chloride is 95.1% and the selectivity of chlorine is 100%.
[0046] Example 4
[0047] The mass content of Ru in the ruthenium-based composite catalyst of this embodiment is 1.5%, the mass ratio of titanium oxide, aluminum oxide and silicon oxide in the composite carrier is 1:1.5:0.3, and the preparation method of the catalyst is as follows:
[0048] Step 1: Add 800g of aluminum sol with a mass concentration of 20% into a colloid mill for grinding at a grinding temperature of 10°C, then add 352g of titanium oxide and 85g of silicon oxide powder, continue grinding for 50 minutes, then add 490g of pseudo-boehmite (aluminum oxide content of 75%) and 103g of silica sol with a mass concentration of 20% and continue grinding for 50 minutes to obtain a slurry; apply the slurry on a ceramic plate, place it in a drying and roasting integrated furnace for heat treatment, that is, first keep it at 300°C for 3h, and then keep it at 800°C for 3h; after heat treatment, scrape off the titanium aluminum silicon oxide on the ceramic plate and seal it for storage.
[0049] Step 2: Add 10000g of 3% graphene oxide aqueous solution to a colloid mill for grinding, then add 6g of sesbania powder, continue grinding for 50min, then add 40.5g of hydrated ruthenium trichloride (ruthenium content is 37%), and continue grinding for 50min; then add 985g of titanium aluminum silicon oxide obtained in step 1 to the colloid mill and continue grinding for 50min, the grinding temperature is 10°C; then increase the grinding temperature to 95°C, concentrate the solution, and as the water evaporates, the solution gradually becomes viscous, and the volume of the final slurry is 20% to 30% of the initial solution volume.
[0050] Step 3: Coat the slurry obtained in step 2 on a ceramic plate, and in a drying and calcining integrated furnace under nitrogen protection, introduce hydrogen after treating at 280°C for 1 hour, so that hydrogen accounts for 20% of the total volume of nitrogen and hydrogen, and keep the constant temperature for 7 hours, then turn off the hydrogen, keep the constant temperature and nitrogen introduction, add air to the nitrogen after 6 hours, and keep the temperature unchanged for oxidation. The initial concentration of the air introduced is 10% of the total volume of air and nitrogen, and the air is increased by 10% every 1 hour until pure air is introduced, and the temperature is kept unchanged. After the pure air is maintained for 12 hours, it is cooled to room temperature to complete the oxidation and obtain an unformed catalyst.
[0051] Step 4: Scrape the unformed catalyst obtained in step 3 off the ceramic plate, add 6% of the mass of the unformed catalyst into a forming liquid, press the tablets, and place them in a drying and calcining integrated furnace for calcination after forming. The calcination temperature is 280°C, maintained for 8 hours, and then cooled to room temperature to obtain the formed catalyst. The mass percentage composition of the forming liquid is: 0.5%, 2% aluminum sol, 3% silica sol, 5% hydrochloric acid and 89.5% water.
[0052] Evaluation of the catalytic performance of the ruthenium-based composite catalyst in this example: The ruthenium-based composite catalyst was crushed and sieved, and particles between 10 and 20 meshes were loaded into a fixed bed reactor, and air was introduced. At the same time, the reaction temperature was increased to 350°C, and the reaction pressure was controlled to be 0.05 MPa. The air was replaced with oxygen. After the temperature and pressure were stabilized, hydrogen chloride gas was introduced, and the volume ratio of oxygen to hydrogen chloride gas was maintained at 2.0:1. The mass space velocity of hydrogen chloride gas was 0.8 h / min. -1 , oxygen and hydrogen chloride gas undergo oxidation reaction on the catalyst to generate chlorine. The results show that the conversion rate of hydrogen chloride is 90.4% and the selectivity of chlorine is 100%.
[0053] Example 5
[0054] The mass content of Ru in the ruthenium-based composite catalyst of this embodiment is 1.9%, the mass ratio of titanium oxide, aluminum oxide and silicon oxide in the composite carrier is 1:1.2:0.2, and the preparation method of the catalyst is as follows:
[0055] Step 1: Add 750g of aluminum sol with a mass concentration of 20% into a colloid mill for grinding at a grinding temperature of 8°C, then add 408.7g of titanium oxide and 75g of silicon oxide powder, continue grinding for 60 minutes, then add 454g of pseudo-boehmite (aluminum oxide content of 75%) and 33.7g of silica sol with a mass concentration of 20% and continue grinding for 60 minutes to obtain a slurry; apply the slurry on a ceramic plate, place it in a drying and roasting integrated furnace for heat treatment, that is, first keep it at 300°C for 3h, and then keep it at 700°C for 3h; after heat treatment, scrape off the titanium aluminum silicon oxide on the ceramic plate and seal it for storage.
[0056] Step 2: Add 9000g of a 2% graphene oxide aqueous solution to a colloid mill for grinding, then add 5g of starch, continue grinding for 60min, then add 51.4g of hydrated ruthenium trichloride (ruthenium content is 37%), and continue grinding for 60min; then add 981g of titanium aluminum silicon oxide obtained in step 1 to the colloid mill and continue grinding for 60min, the grinding temperature is 8°C; then increase the grinding temperature to 95°C, concentrate the solution, and as the water evaporates, the solution gradually becomes viscous, and the volume of the final slurry is 20% to 30% of the initial solution volume.
[0057] Step 3: Coat the slurry obtained in step 2 on a ceramic plate, and in a drying and calcining integrated furnace under nitrogen protection, introduce hydrogen after treating at 300°C for 1 hour, so that hydrogen accounts for 15% of the total volume of nitrogen and hydrogen, and keep the constant temperature for 8 hours, then turn off the hydrogen, keep the constant temperature and nitrogen introduction, add air to the nitrogen after 6 hours, and keep the temperature unchanged for oxidation. The initial concentration of the air introduced is 10% of the total volume of air and nitrogen, and the air is increased by 10% every 1 hour until pure air is introduced, and the temperature is kept unchanged. After the pure air is maintained for 12 hours, it is cooled to room temperature to complete the oxidation and obtain an unformed catalyst.
[0058] Step 4: Scrape the unformed catalyst obtained in step 3 off the ceramic plate, add 34% of the mass of the unformed catalyst into a forming liquid, perform extrusion molding, and place it in a drying and roasting integrated furnace for roasting at a temperature of 300°C for 10 hours, and then cool it to room temperature to obtain a formed catalyst. The mass percentage composition of the forming liquid is: 0.5% sesbania powder, 3% aluminum sol, 2% silica sol, 4% hydrochloric acid and 91.5% water.
[0059] Evaluation of the catalytic performance of the ruthenium-based composite catalyst in this example: The ruthenium-based composite catalyst was crushed and sieved, and particles between 10 and 20 meshes were loaded into a fixed bed reactor, and air was introduced. At the same time, the reaction temperature was increased to 340°C, and the reaction pressure was controlled to be 0.08 MPa. The air was replaced with oxygen. After the temperature and pressure were stabilized, hydrogen chloride gas was introduced, and the volume ratio of oxygen to hydrogen chloride gas was maintained at 3.0:1. The mass space velocity of hydrogen chloride gas was 0.6 h -1 , oxygen and hydrogen chloride gas undergo oxidation reaction on the catalyst to generate chlorine. The results show that the conversion rate of hydrogen chloride is 95.7% and the selectivity of chlorine is 100%.
[0060] Example 6
[0061] The mass content of Ru in the ruthenium-based composite catalyst of this embodiment is 1.6%, the mass ratio of titanium oxide, aluminum oxide and silicon oxide in the composite carrier is 1:1.3:0.3, and the preparation method of the catalyst is as follows:
[0062] Step 1: Add 750g of aluminum sol with a mass concentration of 20% into a colloid mill for grinding at a grinding temperature of 4°C, then add 378g of titanium oxide and 93.5g of silicon oxide powder, continue grinding for 50 minutes, then add 456g of pseudo-boehmite (aluminum oxide content is 75%) and 100g of silica sol with a mass concentration of 20% and continue grinding for 50 minutes to obtain a slurry containing titanium aluminum silicon oxide; coat the slurry on a ceramic plate, place it in a drying and roasting integrated furnace for heat treatment, and perform heat treatment, that is, first keep it at 300°C for 3h, and then keep it at 600°C for 3h; after heat treatment, scrape the titanium aluminum silicon oxide on the ceramic plate and seal it for storage.
[0063] Step 2: Add 9000g of a 2% graphene oxide aqueous solution into a colloid mill for grinding, then add 5g of starch, continue grinding for 50min, then add 43.2g of hydrated ruthenium trichloride (ruthenium content is 37%), and continue grinding for 50min; then add 984g of titanium aluminum silicon oxide obtained in step 1 into the colloid mill and continue grinding for 50min, the grinding temperature is 4°C; then increase the grinding temperature to 95°C, concentrate the solution, and as the water evaporates, the solution gradually becomes viscous, and the volume of the final slurry is 20% to 30% of the initial solution volume.
[0064] Step 3: Apply the slurry obtained in step 2 on a ceramic plate, and in a drying and calcining integrated furnace under nitrogen protection, introduce hydrogen after treating at 320°C for 3 hours, so that hydrogen accounts for 10% of the total volume of nitrogen and hydrogen, and keep the constant temperature for 5 hours, then turn off the hydrogen, keep the constant temperature and nitrogen introduction, add air to the nitrogen after 6 hours, and keep the temperature unchanged for oxidation. The initial concentration of the air introduced is 10% of the total volume of air and nitrogen, and the air is increased by 10% every 1 hour until pure air is introduced, and the temperature is kept unchanged. After the pure air is maintained for 12 hours, it is cooled to room temperature to complete the oxidation and obtain an unformed catalyst.
[0065] Step 4: scrape the unformed catalyst obtained in step 3 off the ceramic plate, add 27% of the mass of the unformed catalyst into a forming liquid, perform extrusion molding, and place the formed catalyst in a drying and roasting integrated furnace for roasting at a temperature of 300°C for 8 hours, and then cool to room temperature to obtain a formed catalyst. The mass percentage of the forming liquid is: 0.5% sesbania powder, 2% aluminum sol, 1% silica sol, 5% hydrochloric acid and 91.5% water.
[0066] Evaluation of the catalytic performance of the ruthenium-based composite catalyst in this example: The ruthenium-based composite catalyst was crushed and sieved, and particles between 10 and 20 meshes were loaded into a fixed bed reactor, and air was introduced. At the same time, the reaction temperature was increased to 320°C, and the reaction pressure was controlled to be 0.09 MPa. The air was replaced with oxygen. After the temperature and pressure were stabilized, hydrogen chloride gas was introduced, and the volume ratio of oxygen to hydrogen chloride gas was maintained at 1.8:1. The mass space velocity of hydrogen chloride gas was 0.7 h / min. -1 , oxygen and hydrogen chloride gas undergo oxidation reaction on the catalyst to generate chlorine. The results show that the conversion rate of hydrogen chloride is 88.4% and the selectivity of chlorine is 100%.
Claims
1. A ruthenium-based composite catalyst for catalyzing the oxidation of hydrogen chloride to produce chlorine, characterized in that: The catalyst is a composite carrier of aluminum oxide, titanium oxide and silicon oxide on which ruthenium is supported. The mass content of Ru in the catalyst is 1% to 1.9%, and the mass ratio of titanium oxide, aluminum oxide and silicon oxide in the composite carrier is 1:0.8 to 1.5:0.2 to 0.
3. The preparation method of the catalyst comprises the following steps: Step 1: adding aluminum sol with a mass concentration of 20% to a colloid mill for grinding, then adding titanium oxide and silicon oxide powders, and continuing to grind for 30 to 60 minutes, and then adding pseudo-boehmite and silica sol and continuing to grind for 30 to 60 minutes to obtain a slurry; The slurry is coated on a ceramic plate and placed in a drying and roasting integrated furnace for heat treatment, wherein the heat treatment is first low-temperature treatment and then high-temperature treatment, the temperature of the low-temperature treatment is 200-400°C and the time is 2-4 hours, and the temperature of the high-temperature treatment is 600-800°C and the time is 2-4 hours; after the heat treatment, the titanium aluminum silicon oxide on the ceramic plate is scraped off and sealed for storage; Step 2: Add the graphene oxide aqueous solution to a colloid mill for grinding, then add Tianqing powder or starch, continue grinding for 30 to 60 minutes, then add hydrated ruthenium trichloride, and continue grinding for 30 to 60 minutes; then add the titanium aluminum silicon oxide in step 1 to the colloid mill and continue grinding for 30 to 60 minutes, the grinding temperature is controlled at 4 to 10°C, and then the grinding temperature is increased to 94 to 98°C, and the solution is concentrated. As the water evaporates, the solution gradually becomes viscous and finally forms a slurry; Step 3: coating the slurry obtained in step 2 on a ceramic plate, treating it in a drying and roasting integrated furnace at 260-320° C. for 1-3 hours under nitrogen protection, introducing hydrogen so that the hydrogen accounts for 5%-20% of the total volume of nitrogen and hydrogen, maintaining the constant temperature for 4-8 hours, then turning off the hydrogen, continuing to introduce nitrogen for 6-10 hours, then introducing air into the nitrogen, maintaining the temperature unchanged for oxidation, and obtaining an unformed catalyst; Step 4: Scrape the unformed catalyst obtained in step 3 off the ceramic plate, add forming liquid, and press into tablets or extrude into strips. After forming, place it in a drying and calcining integrated furnace for calcination at a temperature of 260 to 320°C, maintain for 4 to 10 hours, and cool to room temperature to obtain a formed ruthenium-based composite catalyst.
2. The ruthenium-based composite catalyst for catalyzing the oxidation of hydrogen chloride to produce chlorine according to claim 1, characterized in that: In step 1, the grinding temperature is 4-10°C.
3. The ruthenium-based composite catalyst for catalyzing the oxidation of hydrogen chloride to produce chlorine according to claim 1, characterized in that: In step 1, the mass ratio of the aluminum sol, titanium oxide, silicon oxide, pseudo-boehmite and silica sol is 1.0-2.5:1:0.15-0.25:0.7-1.5:0.08-0.
3.
4. The ruthenium-based composite catalyst for catalyzing the oxidation of hydrogen chloride to produce chlorine according to claim 1, characterized in that: In step 2, the mass concentration of the graphene oxide aqueous solution is 2% to 4%. When concentrated, the volume of the slurry is 20% to 30% of the volume of the initial solution.
5. The ruthenium-based composite catalyst for catalyzing the oxidation of hydrogen chloride to produce chlorine according to claim 1, characterized in that: In step 2, the amount of sesbania powder or starch added is 0.2% to 0.6% of the mass of titanium aluminum silicon oxide, and the amount of graphene oxide aqueous solution added is 9 to 11 times the mass of titanium aluminum silicon oxide.
6. The ruthenium-based composite catalyst for catalyzing the oxidation of hydrogen chloride to produce chlorine according to claim 1, characterized in that: In step 3, the initial concentration of the air introduced is 10% of the total volume of air and nitrogen, and the air is increased by 10% every 1 hour until pure air is introduced, keeping the temperature unchanged. The pure air is maintained for 12 to 24 hours and then cooled to room temperature to complete the oxidation.
7. The ruthenium-based composite catalyst for catalyzing the oxidation of hydrogen chloride to produce chlorine according to claim 1, characterized in that: In step 4, the mass percentage composition of the molding liquid is: 0.5% Tianqing powder or starch, 2% to 3% aluminum sol, 1% to 3% silica sol, 3% to 5% hydrochloric acid and the balance water; the amount of molding liquid added is 5% to 34% of the mass of the unmolded catalyst.
8. Use of the ruthenium-based composite catalyst according to claim 1 for catalyzing the oxidation of hydrogen chloride to produce chlorine, characterized in that: The ruthenium-based composite catalyst is loaded into a fixed bed reactor, and air is introduced. At the same time, the reaction temperature is increased to 310-350°C, and the reaction pressure is controlled to be normal pressure to 0.1MPa. The air is replaced by oxygen. After the temperature and pressure are stable, hydrogen chloride gas is introduced, and the volume ratio of oxygen to hydrogen chloride gas is maintained at 1.5-3:
1. The mass space velocity of hydrogen chloride gas is 0.6-0.8h -1 , oxygen and hydrogen chloride gas undergo oxidation reaction on the catalyst to produce chlorine.
9. Use of the ruthenium-based composite catalyst for catalyzing the oxidation of hydrogen chloride to produce chlorine according to claim 8, characterized in that: The heating rate is 1-3°C / min.
Citation Information
Patent Citations
A method for preparing a catalyst for hydrogen chloride oxidation
CN107952432B
A method for preparing a highly active hydrogen chloride-hydrogenation catalyst
CN109821571B
Application of copper-lanthanum alloy catalyst in the preparation of chlorine by hydrogen chloride oxidation
CN115350707B